IDENTIFICATION OF THE PRESENCE OF DUGONG, SEAGRASS HABITAT, AND THREATS IN THE WATERS OF BANTEN PROVINCE - Khalifa, Muta Ali; Saad, Moch; Santoso, Prakas; Prabowo, Nico Wantona; Jasmine, Agitha Saverti; Dewantara, Esza Cahya (Politeknik Kelautan dan Perikanan Dumai, 2024)
The waters of Banten Province are one of the habitats of Dugong and many other protected species because it is supported by the many seagrass ecosystems found. The purpose of this study was to identify the presence, seagrass beds, dugong, other protected species, and their threats in Banten Waters. Information data regarding the presence of dugong, threats to dugong, community perceptions regarding dugong and seagrass beds, as well as additional information on other protected species (such as turtles, dolphins, sharks and whales) were taken by conducting in-depth interview methods to respondents. The interview questionnaire was based on the CMS-UNEP standardized dugong questionnaire. The number of respondents was determined with a proportion of 70% in locations with strong dugong information and the rest in neighboring locations. The results showed that dugong, dolphins, turtles, sharks and whales were found in Pandeglang Waters. While in Serang Waters dugong, porpoise, dolphin, turtle and whale shark were found. Threats to the life of dugong and other biota in Pandeglang Waters are the presence of gill net fishing gear and sero, if there is a dugong caught, it is not sold for food but sold to Sea World Ancol under the pretext of rescue. There are two threats in Serang: poachers from the Wadas area and the construction of an international port that changes habitat, pollutes, and can cause accidents. Seagrass beds can be found almost along the entire coast of Pandeglang and Serang. The main threat to seagrass beds is environmentally unfriendly coastal change.